2014
DOI: 10.1007/s12272-014-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Dendrobium nobile derived phenanthrenes in LPS-stimulated murine macrophages

Abstract: Dendrobium nobile belongs to the Orchidaceae family and is one of the medicinal herbs used in traditional Chinese medicine as a therapeutic agent for gastrointestinal and cardiovascular diseases. In this study, we separated three phenanthrenes (ephemeranthol A (EA), 1,5,7-trimethoxyphenanthren-2-ol (TP), dehydroorchinol (DO)) from D. nobile, and compared their anti-inflammatory activities. TP is a new phenanthrene compound and its structure was determined from (1)H, (13)C NMR and HR-ESI-MS data. To analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…RAW264.7 cells are mouse macrophages, which can produce a variety of inammatory factors including TNF-a, IL-8, IL-6, IL-1 and inammatory transmitter NO under the stimulation of bacterial products and external harmful substances. 26,27 LPS is the major component of the cytoderm of Gram negative bacteria, which can activate monocyte-macrophage system like RAW264.7 cell, resulting in the release of a large number of pro-inammatory mediators such as TNF-a and IL-1b, causing systemic inammatory response syndrome and further developing into multiple organ dysfunction, failure, damage or even death. 28,29 In this study, LPS was used to induce the cell inammation model.…”
Section: Resultsmentioning
confidence: 99%
“…RAW264.7 cells are mouse macrophages, which can produce a variety of inammatory factors including TNF-a, IL-8, IL-6, IL-1 and inammatory transmitter NO under the stimulation of bacterial products and external harmful substances. 26,27 LPS is the major component of the cytoderm of Gram negative bacteria, which can activate monocyte-macrophage system like RAW264.7 cell, resulting in the release of a large number of pro-inammatory mediators such as TNF-a and IL-1b, causing systemic inammatory response syndrome and further developing into multiple organ dysfunction, failure, damage or even death. 28,29 In this study, LPS was used to induce the cell inammation model.…”
Section: Resultsmentioning
confidence: 99%
“…The eleven known compounds were identified as densiflorol B ( 3 ) [14], 6,7-dimethoxy-phenanthrene-2,5-diol ( 4 ) [27], dehydroorchinol ( 5 ) [8], 1,5,7-trimethoxy-2-phenanthrenol ( 6 ) [8], denthyrsinin ( 7 ) [28], ephemeranthol A ( 8 ) [29], lusianthridin ( 9 ) [30], moscatilin ( 10 ) [18], gigantol ( 11 ) [12], 3-[( 1E )-2-(3-Hydroxyphenyl)ethenyl]-5-methoxyphenol ( 12 ) [31], and (−)-syringaresinol ( 13 ) [19] by comparing their spectroscopic data with the published data (Supplementary Materials Figures S11–S32). Although the known compounds ( 3 – 11 and 13 ) have been isolated from Dendrobium species, the isolation of compound 12 from Dendrobium species has not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…It has been traditionally used to treat lower fever, dryness of throat, gastrodynia due to stomach problem, blurred vision, and atrophy of the tendon and bone due to kidney problems in East Asia [3,4,5]. Previous phytochemical studies on Dendrobium species have reported the isolation of various types of compounds, specifically phenanthrenes as major components [6,7,8,9,10,11,12,13,14]. Phenanthrenes have been reported to have anti-inflammatory [6,7,8], antifibrotic [9], anti-cancer [10,11,12], and antibacterial activities [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Previous phytochemical studies on this plant have revealed that it is rich in phenanthrenes and bibenzyls. [3][4][5][6][7][8][9][10][11] Phenanthrenes possess several therapeutic activities such as anti-inflammatory, 3 antifibrotic, 4 anticancer, 5 and antibacterial activities. 6 Bibenzyls also display diverse biological activities, including antiplatelet aggregation, 7 antiinflammatory, 8 antimigratory, 9 retinal neoangiogenesis inhibitory, 10 and antimutagenic activities.…”
mentioning
confidence: 99%